2022
DOI: 10.3390/genes13020366
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics-Based Identification of Genes Related to Tapetum Degradation and Microspore Development in Lily

Abstract: Lily is a popular and economically ornamental crop around the world. However, its high production of pollen grains causes serious problems to consumers, including allergies and staining of clothes. During anther development, the tapetum is a crucial step for pollen formation and microspore release. Therefore, it is important to understand the mechanism of tapetum degradation and microspore development in lily where free pollen contamination occurs. Here, we used the cut lily cultivar ‘Siberia’ to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…Microspores originate from the microsporocytes or pollen mother cells within the anthers of sorghum plants through the series of intricate cellular events tightly regulated by a network of genetic and hormonal cues, orchestrating the spatial and temporal expression of key developmental genes in a process called microsporogenesis [15,16]. Transcriptional profiling studies have identified several transcription factors, including MYB, bHLH, and MADS-box proteins, as well as epigenetic modifications, such as DNA methylation and histone acetylation being key regulators of the fine-tuning of gene expression during microsporogenesis [17,18]. Moreover, small RNA-mediated gene regulation, plays a pivotal role in controlling the expression of target genes involved in microspore development and differentiation or maturation process which culminates with the deposition of sporopollenin, a complex polymer essential for pollen wall formation and pollen viability [19].…”
Section: Microsporogenesis and Molecular Mechanismsmentioning
confidence: 99%
“…Microspores originate from the microsporocytes or pollen mother cells within the anthers of sorghum plants through the series of intricate cellular events tightly regulated by a network of genetic and hormonal cues, orchestrating the spatial and temporal expression of key developmental genes in a process called microsporogenesis [15,16]. Transcriptional profiling studies have identified several transcription factors, including MYB, bHLH, and MADS-box proteins, as well as epigenetic modifications, such as DNA methylation and histone acetylation being key regulators of the fine-tuning of gene expression during microsporogenesis [17,18]. Moreover, small RNA-mediated gene regulation, plays a pivotal role in controlling the expression of target genes involved in microspore development and differentiation or maturation process which culminates with the deposition of sporopollenin, a complex polymer essential for pollen wall formation and pollen viability [19].…”
Section: Microsporogenesis and Molecular Mechanismsmentioning
confidence: 99%